Prevalence and risk factors associated with intestinal parasitism in children. Ciego de Ávila, 2023 - Magdeline Francisco Castillo; Dayami Sobrado Carrera; Laidelys Alemán Veliz; Damarys Villanueva Souto (Medisur)
Foundation: intestinal parasites are transmissible infectious diseases caused by protozoa and helminths, and children are the most vulnerable age group to these infections. Objective: to determine the intestinal parasitism prevalence and its association with clinical-epidemiological variables. Methods: a cross-sectional descriptive research was carried out, which covered all children from 1 to 14 years of age in the Ciego de Ávila municipality from June to August 2023. A survey, previously validated, was applied to collect clinical-epidemiological data of interest. Fecal samples were collected, which were analyzed using three coproparasitological techniques. Results: the highest prevalence occurred in the South (38.3%) and Center (27.8%) areas. The age group between 5 and 9 years old (40.7%) and the female sex (52.3%) predominated. No association was identified between the presence of symptoms and being parasitized. Inadequate hygienic habits such as not washing hands before eating food, and not washing fruits and vegetables before consuming them, were risk factors associated with intestinal parasitism. The highest frequency of positive samples corresponded to medically important protozoa and commensals, including Endolimax Nana (52.3%) and Entoameba Histolytica (39.5%). Conclusions: a medium prevalence of intestinal parasitism was obtained in the municipality. Inadequate sanitary hygiene habits were identified as risk factors associated with a greater risk of infection, so educational activities for the prevention and control of parasitosis should be increased.